Hubungan Pijat Oksitosin Dengan Pengeluaran Asi Pada Ibu Post Partum Di Praktek Bidan Madiri Rimenda Br Tarigan Kecamatan Medan Denai Tahun 2023 - Ajeng Chintya Permata; Basaria Manurung (NAJ Nursing Applied Journal, 2024)
Exclusive breastfeeding for 6 months and continuing for 2 years in addition to providing adequate complementary foods (MP ASI) has been proven to be an effective intervention that can reduce infant mortality. This study aims to determine the relationship between oxytocin massage and breast milk production in postpartum mothers at the Madiri Rimenda Br Tarigan Midwife Practice, Medan Denai District in 2023. This type of research is research using an analytical survey with a cross sectional method approach. The population was all post partum mothers who visited the Madiri Rimenda Br Tarigan Midwife Practice, Medan Denai District, totaling 34 people. The number of samples used was 34 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 34 respondents, there was an effect of oxytocin massage on breast milk production in postpartum mothers, showing that the p value = 0.000 < 0.05. It is recommended for Health Workers to increase education regarding Exclusive Breastfeeding.